1990
DOI: 10.7326/0003-4819-113-4-308
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Assessing Falls in an Elderly Population

Abstract: Our study suggests that falls are a marker of underlying disorders easily identifiable by a careful postfall assessment, which in turn can reduce disability and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
139
0
8

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(157 citation statements)
references
References 20 publications
5
139
0
8
Order By: Relevance
“…[24][25][26][27][28][29][30][31][32] These studies indicate that prospective payment reduced hospital costs by reducing the average LOS. [24][25][26]29,30 A large study 27,33 of Medicare beneficiaries (n=16,758) in which half were hospitalized prior to prospective payment and half after found that the overall quality of care, measured by comparing the care received to particular standards (ie, not by measures of outcome) and the process of care improved following the introduction of prospective payment. This study and others also found no evidence that mortality increased after prospective payment was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32] These studies indicate that prospective payment reduced hospital costs by reducing the average LOS. [24][25][26]29,30 A large study 27,33 of Medicare beneficiaries (n=16,758) in which half were hospitalized prior to prospective payment and half after found that the overall quality of care, measured by comparing the care received to particular standards (ie, not by measures of outcome) and the process of care improved following the introduction of prospective payment. This study and others also found no evidence that mortality increased after prospective payment was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…In one randomized controlled trial, a focused history and physical assessment by nurse practitioners following a fall resulted in identification of modifiable medical conditions and decreased hospitalization rates over 2 years of follow-up. 406 There is an overwhelming consensus that fall prevention strategies work.Those patients who have already had a fragility fracture deserve proper evaluation, education, and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Residential care dwellers (58,59,82,98,99,(106)(107)(108)(109)110) In long-term care and residential care settings assessment for risk and appropriate multifactorial interventions for all residents (including those with dementia and cognitive impairment) there is some evidence to support: Exercise (83,87,89-98, 102,107 ) Specific exercise programmes work best within a multifactorial fall-prevention programme but there is evidence that they work alone as well.…”
mentioning
confidence: 99%